Understanding Factors that Motivate Participation of Container Ships in the Quiet Sound Voluntary Commercial Vessel Slowdown - Adams, Sara (My University, 2025)
This thesis seeks to understand the factors that motivate container ship participation in the Quiet Sound voluntary vessel slowdown, given that container ships account for the majority of vessel transits and are the largest contributor of anthropogenic underwater noise among target vessels. The goal of this research is to inform and improve program design and engagement with the shipping industry to increase the impact of the slowdown. This qualitative case study developed an analytical framework to understand the impact of various factors on motivation to participate, including: Program characteristics, information sharing and exchange, operational factors, external influences, and intrinsic values. Sustainability reports and websites of 18 shipping lines calling Puget Sound ports, 6 vessel agents, the Ports of Seattle and Tacoma and the Northwest Seaport Alliance were analyzed. Key informant interviews were conducted with representatives from: Shipping lines, a shipping association, pilotage authority, the ECHO program, the Ports of Seattle and Tacoma, and the Northwest Seaport Alliance.
Thesis (Master's)--University of Washington, 2025
Keywords: Environmental studies; Marine affairs